Percutaneous endoscopic gastrostomy feeding in dysphagic hospitalised older people: Clinical outcomes and healthcare professionals' attitudes / Mohamad Hasif Jaafar - Mohamad Hasif, Jaafar (2017)
The purpose of this doctoral thesis was to explore issues surrounding the use of percutaneous endoscopic gastrostomy (PEG) feeding in dysphagic, older people requiring artificial feeding for a variety of medical conditions in an Asian population. Systematic reviews and observational and interventional studies were conducted to explore the perceptions of healthcare professionals (HCPs), and clinical benefits associated with enteral feeding through the PEG route compared to the nasogastric (NG) route. The two systematic reviews conducted evaluated (i) intervention studies evaluating PEG versus NG feeding in older adults with non-stroke dysphagia, and (ii) quantitative and qualitative studies evaluated attitudes and perceptions of HCP towards PEG feeding. Our mixed methods approach therefore included a quantitative assessment using a survey questionnaire, a qualitative analysis of HCPs’ practice and perception of their knowledge, responsibility and documentation followed by a comparative, non-randomized study in relation to NG tube and PEG tube feeding. Our first systematic review highlighted that few studies have compared PEG to NG in non-stroke dysphagia, and meta-analysis did not show any significant benefits of PEG over NG. Following that, our second systematic review highlighted regional variations in acceptability of PEG, which appears to vary according to legal provisions for decision making and funding streams for PEG. Our quantitative survey highlighted that most HCPs would agree to PEG as the preferred route for long-term enteral feeding. However, for those who would not recommend a PEG, they were most likely to perceive reluctance of family members, concerns with procedural risk and cost of PEG insertion as reasons for refusal. The qualitative study supported this finding by revealing several universal barriers, including education, knowledge, communication and team work. A few unique cultural and political barriers had also emerged including the deeply hierarchical work cultures, autocratic approaches to leadership, and lack of funding structures. The impact iv of enteral feeding on patients’ nutritional status, morbidity, and mortality rates was explored. There was a significant reduction in the composite outcome of complication-free survival with PEG feeding compared to NG feeding. Nutritional improvement was seen in both NG and PEG groups, while greater improvement in mid-arm circumference was observed in the PEG group rather than NG group after controlling for potential confounders. Through this we have identified approaches and areas worthy of further study. Our results suggest that there is a need for clinical audit to continue to view and monitor the service delivery process at the local level. Moreover, this research further suggests that there is a need for up-skilling in knowledge and practice among HCPs in order to provide support to patients with PEG and their caregivers. The present research has also supported the development of local multi-agency guidelines on enteral feeding so that more PEG tube use can be promoted and a common approach exists in clinical practice.